2009
DOI: 10.1159/000248992
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of <i>Bifidobacterium lactis</i> on the Growth of Infants: A Pooled Analysis of Randomized Controlled Studies

Abstract: Background/Aims: Breast milk is the best source of nutrition for the growth of the newborn infant. It is therefore essential that mothers who cannot breastfeed or choose not to are provided with alternatives that closely match the composition and functionality of breast milk. This study aimed to investigate the growth effects of probiotic-supplemented formulas on both healthy and vulnerable populations of infants. Methods: A meta-analysis of data from 5 randomized controlled clinical trials that included infan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 39 publications
1
27
0
Order By: Relevance
“…Protective effects could also be attributed to specific bacterial strains [3]; the 2 bacterial strains we used in our study may have had a possible antagonistic effect [7]. We also did not observe any difference in growth rate with the use of probiotics; this is in line with a pooled analysis of previous trials which showed no significant differences in birth weight, length and BMI between infants who received Bifidobacterium lactis- supplemented infant formula and those that did not [8]. Interestingly, our study suggests that later and long-term probiotic supplementation could reduce the risk of allergic diseases.…”
Section: Introductionsupporting
confidence: 84%
“…Protective effects could also be attributed to specific bacterial strains [3]; the 2 bacterial strains we used in our study may have had a possible antagonistic effect [7]. We also did not observe any difference in growth rate with the use of probiotics; this is in line with a pooled analysis of previous trials which showed no significant differences in birth weight, length and BMI between infants who received Bifidobacterium lactis- supplemented infant formula and those that did not [8]. Interestingly, our study suggests that later and long-term probiotic supplementation could reduce the risk of allergic diseases.…”
Section: Introductionsupporting
confidence: 84%
“…When germ-free flies are repopulated with probiotic lactobacilli strains the flies regain their ability to grow at normal rates [62]; and the IGF axis is restored [63]. In humans, Steenhout et al examined the impact of probiotic-supplemented formulas on growth in both healthy and vulnerable populations [64]. They concluded that the probiotic Bifidobacterium lactis has a positive effect on growth in infants born to mothers with human immunodeficiency virus [64].…”
Section: ) Probiotics and Bone Healthmentioning
confidence: 99%
“…Furthermore, in the mentioned study, the addition of either probiotic or synbiotic increased the villus height:crypt depth ratio and villus height in duodenum and resulted in increased digestive and absorptive function of the intestine and expression of brush border enzymes, and nutrient transport systems (Awad et al, 2009). In addition, the results of a pooled analysis of randomized controlled studies indicated that B. lactis may have had a potential benefit of improving growth in a population of vulnerable infants with mothers who were HIV positive where the risk of faltering growth is greater (Steenhout et al, 2009). Another study of preterm infants showed that supplementing infant formula with probiotic decreased intestinal permeability and led to an increase in head growth (Stratiki et al, 2007).…”
Section: Discussionmentioning
confidence: 99%